(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This scientific work examines the main aspects of analyzing and forming the assortment of women’s casual clothing. The study analyzed the diversity of clothing types based on modern fashion trends, women’s needs, and aesthetic requirements. It is also noted that fabric selection, approach to styling, color harmony, and seasonal factors play an important role in shaping the assortment. During the work, existing assortments on the market and consumer preferences were studied, and effective methods for creating an optimal model and assortment were proposed. The results of the research will serve to increase the efficiency of women’s clothing production in light industry enterprises.